(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
We conducted an analysis of the causes of sudden death in the general population and among individuals aged 18 to 40 based on a retrospective study of forensic autopsy data collected over three years. It was established that one of the leading causes of sudden death in young individuals is cardiovascular pathology associated with prior connective tissue inflammation. In the young age group, the primary pathology contributing to a high risk of sudden death is connective tissue inflammation following collagen-related diseases.